An Analysis of Deixis in Lewis Capaldi “Someone You Loved” Song Lyrics - Mahdzurah, Ghany Irfan; Argawati, Ningtyas Orilina (IKIP Siliwangi, 2025)
Deixis is one of pragmatic branch that study about the meaning of pointing something in the language. The research is aim to find out kind of deixis found in “Someone You Loved” song lyrics and to investigate the dominant deixis used in the song lyrics. The researcher choose this song because this song is easy listening and got a positive rating from the listener. Descriptive qualitative research was used to analyze the song. The result of this research showed, types of deixis founded in Lewis Capaldi’s songs of “Someone You Loved”, the deixis are: personal deixis, temporal deixis, and spatial deixis. Deixis was founded in Lewis Capaldi’s songs, which proved that deixis founded in the song lyric were 69 personal deixis, 6 spatial deixis and 12 temporal deixis with the dominant types of deixis was personal deixis with 73% frequency percentage in the song lyric. Thus, the most used deixis that used in Lewis Capaldi’s songs was personal deixis by 79%.